Therapeutic Approaches to Polyglutamine Diseases: Combating Protein Misfolding and Aggregation - Herbst, Martin; Wanker, Erich E. (Current Pharmaceutical Design, 2006)
Polyglutamine diseases are autosomal dominant, late-onset neurodegenerative disorders. Expansion of a polyglutamine (polyQ) tract above a threshold size leads to misfolding and aggregation and eventual intracellular accumulation of the disease-specific protein. To date, only symptomatic treatments of limited effectiveness are available. Various research strategies aim to interfere with known steps in the pathomechanism. Protein misfolding and aggregation probably occur very early in the cascade of pathogenic events and are therefore attractive targets for potential drug treatment. Misfolding of polyQ proteins may either be prevented by drugs that stabilize the native conformation or via induction of cellular chaperones. Several amyloid-binding dyes as well as small molecules that inhibit polyQ protein aggregation have been identified in compound screens and may be entered into drug development. Small molecule inhibitors of further pathogenic phenomena like transcriptional repression, excitotoxicity, mitochondrial dysfunction, and neuronal cell death have been tested in vitro and in vivo. The first drugs have now reached clinical trial stage. More general studies of how putative steps in the pathomechanism can be modulated will yield further insights into the pathogenesis of polyQ disorders.
Keywords: geldanamycin